The Role of ESG and Digitalization Driving Sustainable Agropreneurship in Emerging Market - Aulia, Azwani; Sukmadilaga, Citra; Avianti, Ilya; Rosdini, Dini; Ghani, Erlane K. (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study examines the determinants of Firm Valuein the global agricultural sector from 2017 to 2022 across 37 countries, focusing on the impact of Digital Adoption, Board Gender Diversity (BGD), Multiple Large Shareholders (MLS), and ESG performance. The research highlights the growing importance of sustainable practices and effective governance in agriculture, a sector that is increasingly influenced by market dynamics and environmental challenges. The study aims to understand how these factors contribute to FV, with a particular focus on the roles of governance and sustainability in enhancing corporate performance. The method employed is path analysis in AMOS, which allows for a thorough examination of the relationships among these variables. The results show that Digital Adoption significantly enhances FV by improving operational efficiency, facilitating sustainable practices, and aligning with market trends. Board Gender Diversity contributes to better decision-making and governance, thereby positively influencing FV. In contrast, the presence of MLS negatively affects FV due to governance inefficiencies associated with concentrated ownership. Moreover, strong ESG performance is found to enhance stakeholder relationships and mitigate risks, thereby boosting FV. The study also identifies a gap in the literature regarding the role of digital tools such as AI and blockchain in fostering digital adoption and sustainability. The novelty of this study lies in its cross-country analysis and its consideration of governance structures. The results underscore the significance of sustainable practices and governance in enhancing FV within the agricultural sector.